Clinical practice guidelines for acute and post-acute care of patients with spinal cord injury: a scoping review protocol. (2nd June 2021) - Gregorio, Marianne Pearl; Manhas, Kiran Pohar; Brehon, Katelyn; Vaska, Marcus; Moore, Glenda; O'Connell, Petra; Ho, Chester; Papathanassoglou, Elizabeth
Abstract : Background: Spinal cord injury (SCI) impacts quality of life. Clinical practice guidelines (CPG) for comprehensive SCI care are not completely agreed upon, leading to considerable variability in care and patient outcomes. Aims: We aim to summarise and critically evaluate existing CPGs for the care of patients with SCI at the acute and post-acute phase of their care, and to identify gaps in guidance for nursing and multidisciplinary care. Methods: The scoping review protocol was directed by the Joanna Briggs Institute (JBI) guidelines and Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) reporting guideline. Some 13 databases will be searched for eligible CPGs. Two independent reviewers will screen and extract data using pre-specified eligibility criteria. The quality of CPGs will be appraised using the AGREE II tool.